Prototype Development of Pragmatic Teaching Materials Based on Blended Learning Students of Indonesian Language and Literature Study Program Muhammadiyah University Makassar - Razak, Nur Khadijah; Hamsa, Akmal; Syamsudduha, Syamsudduha (International Journal of Science and Applied Science: Conference Series, 2022)
In the 21 century, colleges are the most impacted institutions by societal dynamics that need a shift in curriculum substance to one that is more adaptable to students' interests, needs, and expectations. The Indonesian Ministry of Education, Culture, Research, and Technology issued a policy Number 754/P/2020, which encourages students to master numerous sciences systematically, so as to produce quality graduates with mastery of soft skills and hard skills, capable of work professionally according to the disciplines they master, and master ICT. Therefore, researcher is interested in creating prototypes of blended learning-based pragmatic teaching materials. Using the Dick and Carey development model, this research is categorized as R&D. The research stage starts from a preliminary study followed by design, development, assessment and revision, and dissemination. The findings revealed that expert validation, small-scale field trials, and large-scale field trials all contributed to the final outcome of the creation of blended learning-based pragmatic teaching materials. Materials and content on pragmatic blended-learning teaching materials consist of 10 learning subjects. There are materials for online learning as well as ones for in-person learning. Each topic contains two major components: learning resources and learning activities. The final outcome of the production of pragmatics teaching materials based on blended learning is certified legitimate, practical, and effective for use in pragmatic learning.